Problematika Regulasi Pendidikan Dan Dampaknya Terhadap Proses Pembelajaran Di Sekolah - Umi Muflichati; Sri Minarti (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
Educational regulations play a crucial role in regulating the implementation of the education system to ensure it aligns with national education goals. However, various problems persist in their implementation, such as rapid policy changes, inconsistencies between regulations and school conditions, and a lack of preparedness among educators to adapt to new regulations. These conditions impact the learning process, including planning, implementation, and evaluation. The purpose of this study is to analyze the challenges faced by educational regulations and their impact on the learning process. The research method used was qualitative with a descriptive approach. Data were obtained through observation, interviews, and documentation within the school environment. The results indicate that the challenges faced by educational regulations cause difficulties for teachers in administering learning, limited time for curriculum implementation, and decreased classroom learning effectiveness. Furthermore, poorly structured regulatory changes also create confusion for schools in implementing educational policies. Educational regulations need to be formulated more consistently, adaptively, and take into account real-world conditions in schools to ensure effective and optimal learning.